Integrating Psychological Perspectives into Islamic Educational Leadership: Toward a Holistic Leadership Framework - Mahalli Mahalli; Khalimatus Sa’diyah; Sukarman Sukarman (Dirasah International Journal of Islamic Studies, 2026)
Existing scholarship on Islamic educational leadership predominantly treats Islamic ethical foundations and psychological theories as discrete domains, leaving a critical gap in understanding how psychological competencies—emotional intelligence, motivation, and conflict management—can be systematically synthesized with Islamic values (amanah, shūrā, uswah hasanah) to produce coherent leadership praxis. This study addresses this gap by developing an integrative theoretical framework bridging Islamic ethical imperatives with psychological insights. Employing qualitative library research with systematic literature review, this study analyzed peer-reviewed articles, scholarly books, and policy documents published 2020–2026, selected through purposive sampling based on relevance to educational leadership, psychology, and Islamic education. Data were analyzed using qualitative content analysis with source triangulation. The findings reveal that Islamic educational leadership is grounded in Qur'anic ethical-spiritual principles; psychological perspectives significantly enhance leadership effectiveness through improved emotional engagement and organizational climate; and critically, the synthesis of Islamic values with psychological principles produces a holistic leadership model that transcends managerial approaches by embedding spiritual accountability within evidence-based behavioral strategies. This integrative model generates adaptive leadership practices capable of addressing digital transformation and institutional complexity while maintaining moral integrity. Theoretical implications: This study contributes a synthesized conceptual framework positioning Islamic educational leadership as simultaneously spiritually grounded and psychologically informed, challenging the binary treatment in existing literature. Practical implications: The framework provides actionable guidance for leadership training in madrasahs, pesantrens, and Islamic schools, emphasizing the development of emotional intelligence alongside ethical character formation.